Differences in Trochlear Morphology from Native Using a Femoral Component Interfaced with an Anatomical Patellar Prosthesis in Kinematic Alignment and Mechanical Alignment - Hull, Maury L.; Howell, Stephen M. (The Journal of Knee Surgery, 2020)
Patellofemoral complications following total knee arthroplasty can be traced in part to alignment of the femoral component. Kinematic alignment (KA) and mechanical alignment (MA) use the same femoral component but align the component differently. Our objective was to determine differences in trochlear morphology from native for a femoral component interfaced with an anatomical patellar prosthesis in KA and MA. Ten three-dimensional femur-cartilage models were created by combining computed tomography and laser scans of native human cadaveric femurs free of skeletal abnormalities. The femoral component was positioned using KA and MA. Measurements of the prosthetic and native trochlea were made along the arc length of the native trochlear groove and differences from native were computed for the medial-lateral and radial locations of the groove and sulcus angle. Mean medial-lateral locations of the prosthetic groove were within 1.5 and 3.5 mm of native for KA and MA, respectively. Mean radial locations of the prosthetic groove were as large as 5 mm less than native for KA and differences were greater for MA. Sulcus angles of the prosthetic trochlea were 10 degrees steeper proximally, and 10 degrees flatter distally than native for both KA and MA. Largest differences from native occurred for radial locations and sulcus angles for both KA and MA. The consistency of these results with those of other fundamentally different designs which use a modified dome (i.e., sombrero hat) patellar prosthesis highlights the need to reassess the design of the prosthetic trochlea on the part of multiple manufacturers worldwide.
Keywords: total knee arthroplasty; femoral component; patellofemoral complications; kinematic alignment; mechanical alignment